Analysis of the Potential of Mukapayung Village as a Sustainable Tourism Destination Based on Sports Tourism - Arief Syaifudin; Hendarmawan; Zulkifli Harahap; Evi Novianti (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2022)
Tourism development in the West Bandung area is currently a serious concern for the local government, one of which is by developing tourist villages. Mukapayung Village, located in Cililin District, is one of the villages designated by the local government as a tourist village. This village has natural beauty with a stretch of rocks that are in harmony with the flow of the river and towering cliffs. This study tries to explore more deeply the potential that Mukapayung village has to be developed into a sportss tourism-based tourism village in West Bandung Regency. The analysis of tourism potential is carried out using a pentahelix approach in order to obtain a picture of the potential of destinations that specifically examines from the aspects of society, government, the role of the media, business actors, and academics so as to support sustainable tourism. This study uses an exploratory qualitative approach. The results of the study obtained an overview that Mukapayung has the potential to be developed as a sports tourism destination by organizing attractions such as: tracking, cycling, climbing, and other sports attractions. A number of tourism components that still need to be developed or improved to support the acceleration of Mukapayung include destination facilities, accommodation, and amenities. As for the management and development of destinations, Mukapayung is currently managed independently by the community through village organizations (Bumdes), without involving various elements such as the tourism office, business actors, academics, and the role of mass media as well as the community and lovers of sportss tourism.